Corporate Governance and Bank Performance : A Joint Analysis of the Static, Selection, and Dynamic Effects of Domestic, Foreign, and State Ownership - Berger, Allen N.; Clarke, George R. G.; Cull, Robert; Klapper, Leora; Udell, Gregory F. (World Bank, Washington, DC, 2012)
The authors jointly analyze the static, selection, and dynamic effects of domestic, foreign, and state ownership on bank performance. They argue that it is important to include indicators of all the relevant governance effects in the same model. "Nonrobustness" checks (which purposely exclude some indicators) support this argument. Using data from Argentina in the 1990s, their strongest and most robust results concern state ownership. State-owned banks have poor long-term performance (static effect), those undergoing privatization had particularly poor performance beforehand (selection effect), and these banks dramatically improved following privatization (dynamic effect. However, much of the measured improvement is likely due to placing nonperforming loans into residual entities, leaving "good" privatized banks.